The existence of fintech as a financing instrument in improving financial inclusion for MSMEs in Sidayu District - Kholid Albar (International Journal on Social Science, Economics and Art, 2023)
In the modern era, people are increasingly opting for technology-driven shopping systems to acquire goods without face-to-face transactions. Financial Technology (fintech) is gaining popularity due to its ease, speed, and user-friendliness. The use of fintech in the business world, particularly in culinary Micro, Small, and Medium Enterprises (MSMEs), has had a positive impact and response in Sidayu District, Gresik Regency. Consumers in the age range of 17-35 years, welcome the existence of this fintech. There is a certain satisfaction that is felt when we follow the development of current technology, ease of transactions and so on. However, there are still challenges in promoting equal adoption of this technology due to limited information and awareness among the community in Sidayu District. Furthermore, the public's interest in this technological innovation is not sufficiently strong, resulting in limited distribution of fintech usage. Based on the results of the study, the existence of Financial Technology or more commonly known as fintech has a role in supporting the increase in inclusion of financing products for the community, especially for MSMEs in Gresik Regency, although this does not guarantee that its development will be comprehensive for areas in Gresik Regency. A SWOT analysis indicates that culinary MSME businesses have high potential for growth and development if business owners implement various marketing strategies tailored to their needs.